(untitled) (Baghdad Science Journal, 2025)
The female Shabout were collected as samples from Dijla river in Baghdad. The oocyte developmental stages were divided in to nine stages, based on nucleus structure , cellular inclusions and ovarian follicle structure ,they are:-( Oogonia stage , Early Perinucleolar Stage , Advanced Perinucleolar Stage , Cortical Alveoli Stage , Primary Yolk Stage , Secondary Yolk Stage , Tertiary Yolk Stage , Migratory Nucleus Stage , Hydration Stage(